Perlindungan Hak Cipta Terhadap Pencipta Lagu Dalam Penggunaan Video Parody Di Youtube - Miranda, Chaileisya (Fakultas Hukum Universitas Islam Indonesia, 2021)
An interesting issue is how the Song Parody and Copyright in Settings in Indonesia. and the next issue is the Copyright Protection of the Inner Song Creator Use of Video Parody on YouTube. This study uses the approach: statute approach, and conceptual approach. Techniques for tracing legal materials using techniques document study (library research), and analysis of the study using qualitative analysis. Results research shows that Copyright Protection Against Songwriters In The use of parody videos on YouTube is based on UUHC, both creators and actors the show can file legal remedies by way of termination and in a civil manner. On termination, the Creator and Performer of the Original Song will report to the minister for parody songs on YouTube that violate copyright so that they cannot be accessed by the public based on article 55 UUHC with. Civilly both the Creator and Performer the original song can file a claim for compensation to the Commercial Court based on article 99 UUHC which must be preceded by peace efforts. Criminally only songwriters only original persons can file criminal charges based on article 113 paragraph 2 UUHC, Meanwhile, performers cannot file criminal charges based on UUHC, except for Article 315 of the Criminal Code if you think it's a parody of a song uploaded on YouTube This caused him to be defamed.